TERTAWALAH SEBELUM TERTAWA DILARANG DALAM POLITIK!: Membayangkan Indonesia lewat Meme Politik Pilpres 2014 - Ridwan Muzir (Universitas Islam Negeri Imam Bonjol Padang, 2015)
This article highlights the use of memes in the political campaigns of presidential elections in 2014. The massmedia inform that public participation increased significantly at that time, one of them through social media.In the initial observation, the expressiony of support was expressed by way of utilizing the existing visualmaterial, plus the technology to knock the opponent. Visual images of opponent processed in a way, bothvisually and textually, allowing so the image used to attack an opponent who has the image. While almost novisual imagery backed candidates were created to express support for him. The cases highlighted in this articleis a political meme of supports in the presidential election 2014. The question to be answered is: what are thedimensions of stereotypical cultural utilized and how those utilized through political meme in the context of aperson's involvement as a citizen of Indonesian culture? Dimensional stereotypical culture here is understoodas a dimension of the stereotype that emerged from religious backgrounds, art, ideology, economic class, race /ethnicity, region (central / regional), social relationships and other relevant socio-political conditions Indonesiahistorically. The aim is to describe public involvement in the political context of Indonesia by using the virtualworld. To answer this question, it will be utilized perspective of critical discourse analysis. An approach thatis commonly used is semiotic.